Pengaruh Pendekatan Contextual Teaching and Learning Berbantuan Geogebra Terhadap Hasil Belajar Siswa SMA PGRI 2 Palembang - Nurjanah, Ika; Ningsih, Yunika Lestaria; Mulbasari, Anggria Septiani (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This study aims to investigate the influence of the Contextual Teaching and Learning (CTL) approach assisted by GeoGebra software on the mathematics learning outcomes of students at SMA PGRI 2 Palembang. The research method used is an experiment with a Posttest-Only Control Design, where the experimental class is taught using the CTL approach with the help of GeoGebra, while the control class uses the CTL approach. The research sample consists of two classes with a total of 54 students, randomly selected from the population of 11th-grade students. Data were collected through learning outcome tests, and data analysis was conducted using the MannWhitney test to determine significant differences between the learning outcomes of the two groups. The research results show that the use of the CTL approach actually resulted in a significant improvement in mathematics learning outcomes compared to the GeoGebra-assisted CTL approach. Additionally, students who learned with this approach showed higher motivation and a more positive attitude towards mathematics learning. These findings indicate that the CTL approach supported by GeoGebra may be a less effective alternative for improving learning outcomes and student engagement in mathematics at SMA PGRI 2 Palembang.